Reconnoitring Guwahati’s FM Landscape: An Analysis of Popular Radio Channels - Florence Handique Rabha, Suresh Chandra Nayak (Journal of Informatics Education and Research, 2025)
The diffusion of FM broadcasting is, in terms of exponential growth, irreversible, and with Guwahati, a southeastern Indian urban centre of eminence, this has been demonstrated to have a strongly felt, transforming impact. This study aims to explore the listening preferences and behaviours of people with respect to popular FM radio stations in the city of Guwahati, where strategic linkages and rapid urbanization make it an epicentre of development for the larger Northeastern region (Misra & Hussain, 2022). Guwahati, being a key education and trade centre, offers a peculiar socio-economic context that has influenced the media consumption habits of this city. The questionnaire will be based on the following aspects: preferences for content, audience structure, the time of day when people listen to the radio, and socio-demographic characteristics. Moreover, the study aims to enhance the understanding of media consumption habits in developed areas, with a specific focus on fast-developing urban centres in India, and Guwahati is the hub of Northeast India (Basumatary & Anand, 2020). With affordable radio receivers becoming widely accessible, the medium experienced a remarkable revival in the public sphere. Rather than being overshadowed by the cable television boom, radio carved its path and thrived, despite scepticism from government bodies regarding its influence on the masses. From rickshaws to mobile phones and cars, FM radio transformed the urban media consumption habits. It became a ubiquitous presence, accessible, portable, and personal. However, amidst the urban frenzy for FM, there remained silent listeners on the margins, often unnoticed. The entry of private players significantly boosted the popularity of FM radio in India. Today, the FM radio market has experienced rapid expansion and significant growth. Its commercial potential is vast, mainly because of its extensive reach from small roadside vendors to corporate professionals; everyone is tuned in. In contemporary society, staying connected and informed has become essential. Media, including radio, now play a vital role in our daily lives, influencing us in ways we may not even be aware of. It shapes our personal and public experiences, our imaginations, emotions, behaviours, preferences, and cultural expressions, such as music, fashion, food, and lifestyle.